Immunological Aspects of Macular Edema after Cataract Surgery in Patients with Diabetes Mellitus - M. A. Frolov; D. V. Lipatov; I. A. Bashina; A. M. Frolov; E. S. Belyaeva (Oftalʹmologiâ)
Cytokines are polypeptides which are produced by a broad range of cells of the body. They play a key role in the formation and regulation of protective reactions. The researchers attempt to find predictors for the development of exudative-inflammatory reaction after surgery. It led to study of the eyes immunological status. It is known that a change of the pro- and anti-inflammatory cytokines balance leads to the blood-ocular barrier dysfunction that increases the inflammatory reaction. It is interesting the blood-ocular barrier has already damaged in diabetic patients. The paper examines the epidemiology, pathogenesis and possible methods of prevention the postoperative cystoid macular edema, presents investigations describing the change in the local cytokine status in patients with diabetes and the association between cytokines concentrations and the severity of diabetic retinopathy. The manuscript has shown possibilities of multiplex analysis, emphasized the features of individual cytokines and angiogenic factors, highlighted cytokines as predictors of macular edema after cataract surgery. The study of the cytokines role in the development of ophthalmic pathology led to the creation the new pathogenetically oriented eye diseases therapy. Further studies of the cytokine status in patients with macular edema after phacoemulsification are needed to determine the possible treatment methods.